Communication Strategy Of Government Public Relations Depok City In Managing Covid-19 Information During Pandemic On Instagram - Desna Aryana Pratiwi; Amri Dunan (International Journal of Educational Research & Social Sciences, 2021)
Multiple crises in aspects of life have occurred due to Covid-19. The infodemic on social media has resulted in government agencies needing to carry out optimal management of government communication media, especially social media. Diskominfo Depok has a communication strategy to deal with Covid-19 information on Instagram. Qualitative research methods with a case study approach, Mc.Luhan's Media Ecological Theory and S.W.O.T Analysis in public relations.The results showed that the implementation of persuasive and contributive communication strategies by Diskominfo on Instagram @pemkotdepok to achieve good public communication and realize the vision and mission of Diskominfo as government public relations. The progress of social media Instagram @pemkotdepok is intensively developed as concrete evidence of Mc. Luhan's assumption in Media Ecology Theory "the medium is the message" and technological progress is very attached to human life. Shows the development of Diskominfo as a communication facilitator. The S.W.O.T analysis used aims to identify the strengths, weaknesses, opportunities, and threats for Diskominfo in carrying out communication strategies on Instagram social media caused by Diskomifo's internal and external factors during the pandemic.